Blockchain System for Transparent Management of Smart Grids: Study and Hybrid Ethereum-Hyperledger Model - LAMBONI, Minlibe; PALANGA, Eyouléki Tcheyi Gnadi; TEPE, Kossi (International Journal of Innovative Research and Scientific Studies, 2025)
The management of smart grids requires enhanced transparency and efficient optimization of energy transactions. While blockchain technology is widely used to ensure traceability and decentralization, existing solutions primarily focus on commercial aspects, often overlooking detailed monitoring of energy flows. This study proposes a hybrid blockchain model combining Ethereum and Hyperledger Fabric to integrate secure transaction execution with real-time energy flow tracking. The adopted approach involves identifying key components of decentralized energy management, conducting a comparative analysis of blockchain architectures, and performing experimental simulations to evaluate their performance in terms of latency, security, and scalability. Specific metrics, such as transaction throughput, block validation time, and energy data granularity, were utilized to assess the efficiency of the proposed model. The results demonstrate that Hyperledger Fabric excels in energy flow monitoring and auditability, whereas Ethereum optimizes transaction execution through its consensus mechanism and broad adoption. The integration of both technologies enables optimal complementarity, ensuring effective interoperability and significantly improving overall system transparency and efficiency. The proposed hybrid model establishes a scalable and resilient architecture that enhances coordination among network participants and optimizes energy governance. It fosters trust among stakeholders by ensuring the integrity and immutability of exchanges while enhancing the management of distributed energy resources. By integrating Ethereum and Hyperledger Fabric, this solution provides an innovative and applicable framework for decentralized energy infrastructures, optimizing transaction management, improving energy flow traceability, and reinforcing the resilience of smart grids against increasing demands for flexibility and sustainability.